Work design growth model: How work characteristics promote learning and development - Parker, Sharon (2017)
This chapter argues that the time is ripe to leverage existing research and develop theory on work design as a vehicle for learning and development. It is common to distinguish between learning processes and learning outcomes. Learning processes include cognitive processes, motivational processes, and behavioral processes. The Work Design Growth Model proposes that work design influences several important learning outcomes through cognitive, behavioral, and affective processes. Of the various elements proposed in this model, theory is most developed and evidence is most compelling in regard to the effect of work design on cognition and skills. The WDGM proposes that work design creates experiences and a social environment that shapes how one sees one's 'self' as well as how one expresses that self. Work design scholars have speculated that work design might affect moral outcomes such as ethical behavior or corruption, yet there has been little articulation of underpinning mechanisms.